Antibodies to coagulase of Staphylococcus aureus crossreact to Efb and reveal different binding of shared fibrinogen binding repeats - Bertoglio, Federico; Ko, Ya-Ping; Thomas, Sheila; Giordano, Liliana; Scommegna, Francesca Romana; Meier, Doris; Polten, Saskia; Becker, Marlies; Arora, Srishtee; Hust, Michael; Höök, Magnus; Visai, Livia (Frontiers in Immunology, 2023)
Staphylococcus aureus pathology is caused by a plethora of virulence factors able to combat multiple host defence mechanisms. Fibrinogen (Fg), a critical component in the host coagulation cascade, plays an important role in the pathogenesis of this bacterium, as it is the target of numerous staphylococcal virulence proteins. Amongst its secreted virulence factors, coagulase (Coa) and Extracellular fibrinogen-binding protein (Efb) share common Fg binding motives and have been described to form a Fg shield around staphylococcal cells, thereby allowing efficient bacterial spreading, phagocytosis escape and evasion of host immune system responses. Targeting these proteins with monoclonal antibodies thus represents a new therapeutic option against S. aureus. To this end, here we report the selection and characterization of fully human, sequence-defined, monoclonal antibodies selected against the C-terminal of coagulase. Given the functional homology between Coa and Efb, we also investigated if the generated antibodies bound the two virulence factors. Thirteen unique antibodies were isolated from naïve antibodies gene libraries by antibody phage display. As anticipated, most of the selected antibodies showed cross-recognition of these two proteins and among them, four were able to block the interaction between Coa/Efb and Fg. Furthermore, our monoclonal antibodies could interact with the two main Fg binding repeats present at the C-terminal of Coa and distinguish them, suggesting the presence of two functionally different Fg-binding epitopes.